Risk of ischemic stroke in patients with end-stage renal disease receiving peritoneal dialysis with new-onset atrial fibrillation. Issue 12 (2nd December 2020) - Lee, Yin-Hao; Chen, Yung-Tai; Chang, Chun-Chin; Hsu, Chien-Yi; Su, Yu-Wen; Li, Szu-Yuan; Huang, Chin-Chou; Leu, Hsin-Bang; Huang, Po-Hsun; Chen, Jaw-Wen; Lin, Shing-Jong
Abstract : Background: The clinical effect of atrial fibrillation (AF)-related ischemic cardiovascular events in patients undergoing peritoneal dialysis (PD) remains uncertain. This study aimed to investigate the risk of ischemic events in patients undergoing PD with new-onset AF compared with that in patients without AF and ascertain the association between the CHA2 DS2 -VASc score and risk of ischemic stroke. Methods: This nationwide, population-based cohort study used data from Taiwan's National Health Insurance Research Database from 1998 to 2011 for patients receiving PD with or without new-onset AF. The clinical endpoints included ischemic stroke, all-cause death, and in-hospital cardiovascular death. Results: Patients undergoing PD with new-onset AF (N = 505) had significantly higher risks of ischemic stroke (adjusted hazard ratio [aHR], 1.98; 95% CI, 1.40-2.80), all-cause death (aHR, 1.61; 95% CI, 1.40-1.85), and in-hospital cardiovascular death (aHR, 1.82; 95% CI, 1.50.2.21) compared with those in patients undergoing PD without AF. After considering in-hospital death as a competing risk, AF remained associated with an increased risk of ischemic stroke (hazard ratio [HR], 1.67; 95% CI, 1.17-2.37). The CHA2 DS2 -VASc score was associated with the risk of ischemic stroke (HR, 1.28; 95% CI, 1.12-1.46). Conclusion: The risks of ischemic stroke, all-cause death, and in-hospital cardiovascular death were significantly higher in patients undergoing PD with AF than those in patients without AF. The CHA2 DS2 -VASc score remained associated with the risk of ischemic stroke in patients undergoing PD with AF.